Impact strength and flexural properties enhancement of methacrylate silane treated oil palm mesocarp fiber reinforced biodegradable hybrid composites - Eng, Chern Chiet; Ibrahim, Nor Azowa; Zainuddin, Norhazlin; Ariffin, Hidayah; Wan Yunus, Wan Md Zin (Hindawi Publishing Corporation, 2014)
Natural fiber as reinforcement filler in polymer composites is an attractive approach due to being fully biodegradable and cheap. However, incompatibility between hydrophilic natural fiber and hydrophobic polymer matrix restricts the application. The current studies focus on the effects of incorporation of silane treated OPMF into polylactic acid (PLA)/polycaprolactone (PCL)/nanoclay/OPMF hybrid composites. The composites were prepared by melt blending technique and characterize the composites with Fourier transform infrared spectroscopy (FTIR), thermogravimetric analysis (TGA), and scanning electron microscopy (SEM). FTIR spectra indicated that peak shifting occurs when silane treated OPMF was incorporated into hybrid composites. Based on mechanical properties results, incorporation of silane treated OPMF enhances the mechanical properties of unmodified OPMF hybrid composites with the enhancement of flexural and impact strength being 17.60% and 48.43%, respectively, at 10% fiber loading. TGA thermogram shows that incorporation of silane treated OPMF did not show increment in thermal properties of hybrid composites. SEM micrographs revealed that silane treated OPMF hybrid composites show good fiber/matrix adhesion as fiber is still embedded in the matrix and no cavity is present on the surface. Water absorption test shows that addition of less hydrophilic silane treated OPMF successfully reduces the water uptake of hybrid composites.